Urban Flooding in Vancouver, Canada - Pallathadka, Arun (Integrated Journal for Research in Arts and Humanities, 2023)
Flooding can have devastating, long-lasting, and costly consequences, including the loss of life and displacement of communities. This review report summarizes the background, causes, and management practices of various urban flooding forms and mitigation efforts in Vancouver, British Columbia (BC) which is located on the Western part on the Pacific coast of Canada. The report makes use of existing literature to understand the flooding phenomena in Vancouver. The city is unique from a flood planning or management perspective because the city is vulnerable to every type of major flooding event, including pluvial, fluvial, and coastal flooding. Nevertheless, Vancouver is considered a globally sustainable city. As such, this report reviews various articles and research to determine the background and causes of various forms of floods experienced in Vancouver and the management practices put in place to mitigate flooding in the city. The study identifies measures in place to address every type of flooding event.